2013
DOI: 10.1371/journal.pone.0067186
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of the Functions of Lysine Acetylation in the Regulation of Tat Activity

Abstract: The Tat protein of HIV-1 has several well-known properties, such as nucleocytoplasmic trafficking, transactivation of transcription, interaction with tubulin, regulation of mitotic progression, and induction of apoptosis. Previous studies have identified a couple of lysine residues in Tat that are essential for its functions. In order to analyze the functions of all the lysine residues in Tat, we mutated them individually to alanine, glutamine, and arginine. Through systematic analysis of the lysine mutants, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Tat acetylation has been characterized to be involved in the regulation of Tat-mediated apoptosis [ 15 , 23 ]. Moreover, Tat86 has been reported to trigger slightly more apoptosis in CD4 + T cells than the full-length form [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tat acetylation has been characterized to be involved in the regulation of Tat-mediated apoptosis [ 15 , 23 ]. Moreover, Tat86 has been reported to trigger slightly more apoptosis in CD4 + T cells than the full-length form [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tat acetylation has been well characterized to be fine-tuned by histone acetyltransferases (HATs) and histone deacetylases (HDACs) at specific lysine residues and is involved in the regulation of Tat activities [ 1 , 4 , 9 14 ]. The mutation of certain lysine residues in Tat significantly affects Tat activities such as transactivation of transcription and induction of apoptosis [ 15 ]. Given that ubiquitination is another posttranslational modification of lysine residues, it is reasonable to speculate that the influences on Tat activities caused by lysine mutation may be partially attributed to altered ubiquitination of Tat.…”
Section: Introductionmentioning
confidence: 99%
“…TA of juice sacs was titrated with 0.1 mol/l NaOH to the end point at pH 8.2 according to the method described by He et al (2013). TSS was measured using a digital hand-held refractometer (PR101-α, Atago, Japan).…”
Section: Ta and Tss Measurementmentioning
confidence: 99%
“…In addition to p300, the hGCN5 HAT acetylates both K50 and K51 residues in vitro and significantly enhances Tat‐mediated transcription of HIV LTR . Indeed, mutational analysis aiming to neutralize the electrical charge of lysine and block acetylation by substitution with the alanine residue demonstrated that acetylation of K50 exclusively regulates Tat transactivation activity (Figure ) …”
Section: Posttranslational Modifications Of the Basic Domain Regulatementioning
confidence: 99%
“…109 Indeed, mutational analysis aiming to neutralize the electrical charge of lysine and block acetylation by substitution with the alanine residue demonstrated that acetylation of K50 exclusively regulates Tat transactivation activity (Figure 2). 110 Proteomic analysis and in vivo experiments showed that Tat acetylated at K50 and K51 residues preferentially binds p32, an inhibitor of splicing factor ASF/SF-2, and mediates its transport to the viral promoter, thus regulating the splicing pattern of HIV-1. 111 Acetylation also decreases cellular uptake of Tat-derived peptides acetylated at either K50 or K51 positions.…”
Section: Acetylationmentioning
confidence: 99%